2016
DOI: 10.1016/j.cmi.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Common skin infection due to Panton–Valentine leucocidin-producing Staphylococcus aureus strains in asylum seekers from Eritrea: a genome-based investigation of a suspected outbreak

Abstract: Since late 2014, multiple cases of abscesses and boils due to methicillin-susceptible Staphylococcus aureus (MSSA) expressing the Panton-Valentine leucocidin (PVL) were observed in Eritrean asylum seekers in Lausanne, Switzerland. Strains isolated from infected Eritrean and non-Eritrean patients were compared by whole genome sequencing to determine whether these numerous cases result from an outbreak. The genome of S. aureus PVL-producing strains were sequenced and compared. Clinical and epidemiological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In the present study many patients reported a past medical history typical of PVL-SA patients-recurrent skin abscess that often required incision and drainage and reporting other affected patients in their immediate environment. PVL-SA-positive patients are often symptomatic for several months, before they are finally diagnosed and treated for PVL-SA [16,[26][27][28][29]. Our results thus underscore earlier work that shows that a diagnosis can be challenging in areas with low PVL-SA prevalence [6,30].…”
Section: Plos Onesupporting
confidence: 83%
“…In the present study many patients reported a past medical history typical of PVL-SA patients-recurrent skin abscess that often required incision and drainage and reporting other affected patients in their immediate environment. PVL-SA-positive patients are often symptomatic for several months, before they are finally diagnosed and treated for PVL-SA [16,[26][27][28][29]. Our results thus underscore earlier work that shows that a diagnosis can be challenging in areas with low PVL-SA prevalence [6,30].…”
Section: Plos Onesupporting
confidence: 83%
“…In our cross-sectional study, the MRSA colonization rate between refugee centres ranged from 2.4% to 25.4%. The high rate of PVL positive MRSA strains is interesting, and a recent comparison between Eritrean and Non-Eritrean patients with common skin infections found a higher percentage of PVL in MSSA of Eritrean patients as well [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Higher MRSA and MDRE carriage rates in asylum seekers were described before [15,16] as was the presence of PVL in asylum seeker strains [17,18]. Reinheimer et al [15] detected a 61% MDRO rate in refugee patients admitted to a University Hospital.…”
Section: Discussionmentioning
confidence: 89%